2005
DOI: 10.1103/physrevb.71.205308
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal conductance in nanowires at low temperatures: Breakdown and recovery of quantization

Abstract: The quantization of lattice thermal conductance g normalized by g 0 = 2 k B 2 T /3h ͑the universal quantum of thermal conductance͒ was recently predicted theoretically to take an integer value over a finite range of temperature and then observed experimentally in nanowires with catenoidal contacts. The prediction of this quantization by Rego and Kirczenow ͓Phys. Rev. Lett. 81, 232 ͑1998͔͒ relies on a study of only dilatational ͑longitudinal͒ vibrational mode in the wires. We study the thermal conductance in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
(22 reference statements)
2
29
1
Order By: Relevance
“…Below 1 K, the thermal conductance decreases below the value of the universal thermal conductance as expected in different models at intermediate temperature. 15,24 Only one sample (P1) exhibits a thermal conductance that is relatively close to four times the universal quantum of thermal conductance (4K q ) as predicted by Rego and Kirczenow,14 and in a work by Tanaka et al 15 However, this is not a general behavior because samples P2 and P3 have a thermal conductance even lower than in the case of the abrupt junction. The dispersion of the experimental results is intriguing because it only occurs for temperature below 1 K. This may be due to varying roughness from one sample to the other, giving different value of mean free path.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Below 1 K, the thermal conductance decreases below the value of the universal thermal conductance as expected in different models at intermediate temperature. 15,24 Only one sample (P1) exhibits a thermal conductance that is relatively close to four times the universal quantum of thermal conductance (4K q ) as predicted by Rego and Kirczenow,14 and in a work by Tanaka et al 15 However, this is not a general behavior because samples P2 and P3 have a thermal conductance even lower than in the case of the abrupt junction. The dispersion of the experimental results is intriguing because it only occurs for temperature below 1 K. This may be due to varying roughness from one sample to the other, giving different value of mean free path.…”
mentioning
confidence: 52%
“…A way to improve the thermal contact consists in profiling the shape at the interface nanowire-thermal reservoir. Rego and Kirczenow, 14 and then Tanaka, Yoshida, and Tamura, 15 demonstrated that a catenoidal profile allows a transmission coefficient close to one for a large range of frequencies. In this particular case, and for the massless mode, the thermal conductance becomes an integer multiple of K q ¼ p 2 k 2 B T=3h, known as the universal quantum of thermal conductance.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The situation is similar to the SV mode. Then, the mixing of P and SV modes occurs and could lead to the appearance of the more modes [35,56]. However, considering our assumption that regions I, II, and III have the same thickness and is small with respect to the other dimensions and also to the wavelength of the elastic waves, the horizontally polarized shear SH mode are decoupled from the phonon mode P (or SV ).…”
Section: Model and Formalismmentioning
confidence: 97%
“…[17,18] Clearly alternative approaches have to be explored in order to open multiple phononic channels.…”
Section: Introductionmentioning
confidence: 99%